Optimal Capital-Gains Taxation under Limited Information - Green, Jerry R.; Sheshinski, Eytan (Journal of Political Economy, 1978)
Taxation of capital gains at realization may distort individuals' decisions regarding holding or selling during an asset's lifetime. This creates the problem of designing a tax structure for capital gains so as to induce efficient patterns of holding an selling. Several tax structures are explored in this paper. Linear taxation, at rates which rise with the holding period, can achieve the first best, even under the conditions of limited information that we postulate. The form of the optimal tax is independent of the stochastic structure of rates of return. We also derive the optimal nonlinear tax under the constraint that it be independent of the holding period. Second-best tax rules are examined. Results in a two-period model are contrasted with those in a continuous time framework. Also treated is the case in which the returns to the asset under consideration depend on the aggregate quantity invested